Identification of driving factors in farm profitability and the implications of a transition from conventional to organic row crop production - Carls, Emily (Kansas State University, 2019)
Management decisions during times of relatively low net farm income have become the focus of recent research and will likely continue to be important in the future. Volatile net farm income, low commodity prices combined with relatively high input costs have deteriorated farm incomes over the last several years. Extension personnel have been working to support producers in improving profitability to provide research, guidance, and software tools to aid in farm-management decision making. Understanding the factors of production that have significant impact on profitability can help producers focus their efforts during times of low net farm income as well as help extension personnel to make better recommendations for producers. Research also indicates that diversification of enterprises can serve as a risk mitigation tool in order to stabilize net farm income over time. Suggesting a primarily row crop producing farm could benefit from more consistent profits by diversifying their operation. One such diversification tactic is transitioning a portion of acreage to organic production. Over the past decade, the organic industry has gained popularity among both consumers and producers. Some profit-maximizing farmers producing cops under conventional practices may consider producing organic crops if consumers are willing to pay a premium sufficient to offset organic production and transition costs. Current organic standards require a three-year transition period from conventional practices in addition to strict production requirements before the crop can be labeled as “organic”. Organic crop rotations are required to include the following: 1) maintain/improve soil organic matter, 2) control pests, 3) regulate plant nutrients, and 4) incorporate erosion control methods. Demand for organically produced food has continued to increase, causing producers to consider transitioning to organic production despite the challenges associated with the transition. This two-part study sought to understand factors affecting the profitability of conventional producers as well as analyze the profitability of transitioning to organic row crop production.
Keywords: Linear program; Logit model; BinomialOrganic